PENGARUH ARTIS HIJRAH TERHADAP PERUBAHAN DIRI FOLLOWERS INSTAGRAM @KAJIANMUSAWARAH (Penamas, 2021)
This study aims to describe and analyze the influence of the hijrah of the artist to change themselves followers Instagram @kajianmusawarah. This research uses the Descriptive Qualitative method with data collection techniques through interviews, online questionnaires online, and documentation. Object in this research is followers of Instagram @kajianmusawarah. The results of this study conclude: first, that many of the fans were affected by the emigration of the artist. It is shown from the turn of the artist who becomes a new phenomenon that can encourage someone to emigrate. Second, the Influence of the hijrah of the artist to the fan can be seen from the changes yourself, a fan who tends to the positive direction in the form of self-change. Third, based on the theory of George Herbert Mead claimed that the self develops through two stages, namely a person internalizes the attitude of other people towards him, and internalizes the norms of society. Change fans of the specialized appearance, the thought of the religious, and social attitudes. It is adjusted with the theory of Andi Hikmawati Jonah, who said that in general hijrah interpreted with three changes that occur in her, that style of dress (appearance), behavioral (social attitudes), and an increase in religious knowledge (thinking religion).
Keywords: Fenomena, Hijrah Artis, Perubahan Positif, Followers Instagram @kajianmusawarah